Answer:
x^2 -x -2 = (x -2)(x +1)
Step-by-step explanation:
To factor x^2 -x -2, you look for factors of -2 that have a sum of -1:
-2 = (-1)(2) = (1)(-2) . . . . . the latter pair has a sum of -1
Then these are the constants in the binomial factors:
x^2 -x -2 = (x +1)(x -2)
_____
<em>Comment on the question</em>
The fact that x^2 +3x -4 is modeled with algebra tiles seems to be irrelevant to the question that is actually asked.
Answer:
vertical angles b= 86
Step-by-step explanation:
b is equal to 86 since the angles are vertical angles
I did this to get 47.5 as the answer not 47 im not sure why but i did (61-7+7×1/2)+17 using the PEMDAS please excuse my dear aunt sally
parenthesis exponents multiply divide add subtract
Answer:
Step-by-step explanation:
In vertex form, the equation is
y = a(x-h)^2 + k
So just read off the values!